Identification, assessment and recognition of non-formal learning in Greece - Turner, Caroline [Verfasser] (Office for Official Publications of the European Communities, 2000)
This report is the Greek contribution to CEDEFOP's project on identification, assessment and recognition of non-formal learning, which was initiated in 1997. Studies in this field have been conducted in a majority of Member States of the European Union (EU) as well as the European Economic Area (EEA), with only Luxembourg and Iceland not yet included. The report begins by providing a picture of the national debate encompassing questions of identification, assessment and recognition of non-formal learning in Greece, including means and motives, areas of agreement and conflict. It goes on to describe methodologies and systems that already exist, including particular sectoral approaches, and those that are proposed to come into play, on the basis of viewpoints and debates involving social partners, education authorities, training institutes and government. Links between initiatives related to the assessment of non-formal learning and the national qualification standards/framework are investigated and reference made to areas of importance and concern. Finally, the effectiveness, legitimacy and validity of existing methods and experiences are assessed, including the issues of mobility and visibility. Gaps and weaknesses are highlighted and reflections on the future expressed. (BIBB-Doku)
Keywords: S 2.2.4.4 Anerkennung non-formaler Qualifikationen; S 2.2.4.3 Zertifizierung; L 2.1.1 Informelles Lernen; L 2.1.3 Erfahrungslernen; I 2.2.1 Westeuropa; Anerkennung; Zertifizierung; Qualifikation; Informelles Lernen; Lernen am Arbeitsplatz; Erfahrungsorientiertes Lernen; Griechenland